Determination of the Stability Constants Comlexes of Metformin Hydrochloride With Cu(II), Cd(II) and Zn(II) - (:unkn) unknown (INT JOURNAL PHARMACEUTICAL RESEARCH & ALLIED SCIENCES, 2020)
In the present work, binary complexes of Copper(II), Cadmium(H) and Zinc(II) with metformin hydrochloride have been studied potentiometrically. Stability constants of binary complex systems have been estimated by the method proposed by Irving-Rossotti at 25 degrees C and 0.11M ionic strength (NaClO4) in aqueous solution. The conditional formation constants of the complexes formed between ligand and metal were calculated according to pH function. The maximum values of the conditional formation constants were found to be in accordance with the mixed metal-ligand complex formation constants in a given pH region. In addition to these, the molar fractions were calculated using the formation constants of the mixed metal-ligand complexes. As a result of the experimental study, the values of stability constants of metal-ligand complexes at 25 degrees Care as noted below: logK(1)=8.45; logK(2)=8.30 for Zn(II)-Metformin hydrochloride; logK(1)=8.78 ; logK(2)=8.00 for Cu(II)-Metformin hydrochloride: logK(1)=8.18; logK(2)=7.36 for Cd(II) - Metformin hydrochloride.
Keywords: Metformin hydrochloride; Zinc(II); Copper(II); Cadmium(II) and metal-ligand complex; stability constants